Technical And Internal Load Responses in 3-A-Side Full-Court Basketball Games: The Effects of Coaches' Verbal Feedback - Elif Mengi; B. Utku Alemdaroglu; Yusuf Koklu; A. Gokce Erturan (European Journal of Human Movement, 2023)
The aim of the current study was to examine the acute effects of three different feedback conditions (positive feedback, negative feedback and no feedback) on heart rate, lactic acid, rate of perceived exertion responses and frequencies of technical actions on basketball players during 3-a-side full-court games. Twelve young basketball players (Mean age: 16.5 ± 1.5 years; height: 181± 5.9 cm; body mass: 71.4 ± 7 kg; training experience: 5.4 ± 2.1 years) voluntarily participated to the study. The players underwent anthropometric measurements followed by the Yo-Yo intermittent recovery test level 1. Then, players performed 3-a-side full-court games under three different conditions with positive verbal feedback, negative verbal feedback and no feedback randomly at 2-day intervals. Repeated measures ANOVAs were used to assess differences among responses to 3-a-side full-court games in terms of heart rate, lactic acid, rate of perceived exertion responses and the number of technical actions performed. No significant differences were found between the three feedback conditions nevertheless lactic acid results showed clinical significance in the negative feedback group (5.4±1.7) compared to the group without feedback (6.5±1.8). The findings of this study reveal that positive, negative verbal feedback given by the coach or no feedback does not have an acute effect on basketball players' game performance and internal load responses.